1999
DOI: 10.1530/eje.0.1400264
|View full text |Cite
|
Sign up to set email alerts
|

Risk of iodine-induced thyrotoxicosis after coronary angiography: an investigation in 788 unselected subjects

Abstract: In this study, the risk of iodine-induced thyrotoxicosis in unselected patients from an iodine-deficient area was investigated. The patients were consecutively enrolled. Thyroid hormone values and urinary iodine excretion were determined before, as well as 1, 4 and 12 weeks after iodine contamination by coronary angiography. Two of 788 unselected patients developed hyperthyroidism within 12 weeks. The two patients did not belong to a risk group for iodine-induced thyrotoxicosis (i.e. old people, patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 14 publications
2
34
0
6
Order By: Relevance
“…[21][22][23][24][25][26] To address these limitations, we conducted a nested casecontrol study to assess the association between ICM exposure and incident thyroid dysfunction.…”
Section: See Invited Commentary and Editor' S Note At End Of Articlementioning
confidence: 99%
“…[21][22][23][24][25][26] To address these limitations, we conducted a nested casecontrol study to assess the association between ICM exposure and incident thyroid dysfunction.…”
Section: See Invited Commentary and Editor' S Note At End Of Articlementioning
confidence: 99%
“…Iodine-induced hyperthyroidism has been reported in patients with a variety of underlying thyroid diseases, but primarily occurs in individuals with nodular thyroid disease (9,10). Martin et al showed development of hyperthyroidism after the use of contrast agents (11).…”
Section: Introductionmentioning
confidence: 99%
“…Goiter was present in 63% of the patients and the majority of them were elderly. In a large study in unselected patients, only 2 of 788 developed hyperthyroidism within 12 weeks of coronary angiography [14]. Administration of non-ionic iodinated contrast medium to 102 euthyroid patients did not lead to hyperthyroidism in any patient despite the large number of nodularly transformed glands and patients with goiter [15].…”
Section: Clinical Studies Of Contrast Media Induced Thyrotoxicosismentioning
confidence: 90%